RANCANGAN PRIMER SPESIFIK GEN MACROPHAGE MANNOSE RECEPTOR (MMR) UNTUK POLYMERASE CHAIN REACTION (PCR) DAN SEKUENSING DEOXYRIBO NUCLEIC ACID (DNA) - Yani Triyani; Nurizzatun Nafsi; Lelly Yuniarti; Nanan Sekarwana; Endang Sutedja; Dida Ahmad Gurnida; Ida Parwati; Bachti Alisjahbana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
The order (sequencing) determinationof DeoxyribonucleicAcid (DNA) bases is the gene’s most basic information, using the methodof Polymerase Chain Reaction (PCR) as its stage. A key factor of successful detection by PCR is specific PCR primer design choice. Thedetection of diversity of Mycobacterium Mannose Receptor (MMR) gene, responsible for recognizing mannosylated antigen structureof Mycobacterium tuberculosis (M.tb) by DNA sequencing of exon 7 chromosome 10p12, related to susceptiblity for PulmonaryTuberculosis(TB), was first performed in China in 2012. The purpose of this study was to find specific primerfromboth design originatedfrom the research in China/primer I and my own design/primer IIby using Primer3 software. This study was based on 10 healthy subjectsand was a preliminary study of a research titled. The Relationship of Single Nucleotide Polymorphisms (SNPs) of Macrophage MannoseReceptor Gene to Pulmonary Tuberculosis Cases. The examination materials consist of 3 mL of EDTA blood and DNA extraction from itsbuffy coat. The resulting DNA was processed by PCR to amplify MMR gene with primer I and II. The primer I successfully amplified DNAfragments up to 780bp while primer II only 329 bp. The MMR gene DNA sequencing analysis was performed on the amplification resultof both kinds primers by using DNA Baser and Ensembl−BLAST software. The results were different, DNA sequencing result by using theprimer I was found in several chromosomes and also in several loci. Whereas, by using the primer II, it was only found in chromosome10 and in the same locus. Based on this study, it can be concluded that the specific primer design is one of the most important factorsin the success of DNA sequencing.